Synthesis and Antileishmanial Activity of Lipophilic Aromatic Aminoalcohols - Roberta Novaes Reis Corrales; Liliane Sena Pinheiro; Elaine Soares Coimbra; Adilson David Da Silva; Mireille Le Hyaric (The Scientific World Journal)
In this work, we report on the preparation and evaluation of the in vitro antileishmanial activity of a series of lipophilic aromatic aminoalcohols. All compounds were assessed for their in vitro activity against promastigotes of three Leishmania species The most lipophilic aminoalcohols bearing an aliphatic moiety with eight to 12 carbon atoms displayed a good activity against L. amazonensis and L. major, and two of them also showed antiproliferative activity against L. chagasi. The best results were obtained for the N-dodecanoyl ethylenediamine derivative and for N-decyl aminoalcohol (IC50 = 5.2 and 0.7 μM, respectively).